The Talking Stick's Impact: A Study on Improving Second- Graders' English Speaking Skills - Chantika, Mayang; Suparmi; Dania , Rahma; Alhusna, Asma (English Education and Applied Linguistics Journal (EEAL Journal), 2025)
This study investigated the effectiveness of the Talking Stick method in improving the speaking skills of students at SMP N 2 Padang, addressing common issues like low proficiency, anxiety, and poor communication. Using a quantitative pre-experimental design, a single group of 32 students from class VIII.1 received a pre-test and a post-test. The results showed a significant improvement, with the average score increasing from 48.59 on the pre-test to 75 on the post-test. Statistical analysis confirmed this finding, as the calculated t-test value of 23.893 was significantly greater than the t-table value of 2.042, leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha). The significance of these findings lies in their ability to provide empirical evidence that the Talking Stick method is a highly effective, data-backed tool for enhancing student speaking skills. This research offers a practical, actionable solution for teachers facing similar challenges in their classrooms and contributes to the existing body of literature by validating the method's effectiveness in a specific, localized context.